2016
DOI: 10.1007/s10339-016-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced music sensitivity in 9-month-old bilingual infants

Abstract: This study explores the influence of bilingualism on the cognitive processing of language and music. Specifically, we investigate how infants learning a non-tone language perceive linguistic and musical pitch and how bilingualism affects cross-domain pitch perception. Dutch monolingual and bilingual infants of 8–9 months participated in the study. All infants had Dutch as one of the first languages. The other first languages, varying among bilingual families, were not tone or pitch accent languages. In two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…Behavioral data have demonstrated that non-tone learning infants are able to discriminate the same contrast around 18 months, and infants’ tonal sensitivity is likely to be acoustic rather than linguistic ( Liu and Kager, 2014 , 2017a ). Following previous studies, we predicted that listeners may retain a certain degree of acoustic perception of non-native tones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral data have demonstrated that non-tone learning infants are able to discriminate the same contrast around 18 months, and infants’ tonal sensitivity is likely to be acoustic rather than linguistic ( Liu and Kager, 2014 , 2017a ). Following previous studies, we predicted that listeners may retain a certain degree of acoustic perception of non-native tones.…”
Section: Discussionmentioning
confidence: 99%
“…Children exposed to a multilingual environment, for instance, have a more challenging task than their monolingual peers, with more sound categories to acquire in the same phonetic space ( Kuhl et al, 2008 ). However, bilingual children have been shown to outperform monolinguals when detecting language changes ( Kuipers and Thierry, 2012 ), perceiving native and non-native speech contrasts ( Shafer et al, 2011 ; Petitto et al, 2012 ; Liu and Kager, 2016 , 2017a ), and learning words ( Graf Estes and Hay, 2015 ; Singh, 2017 ), regardless of the fact that they may not receive as much language input. The bilingual advantage may thus be the result of a more challenging learning environment which leads to heightened sensitivity across domains ( Liu and Kager, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… (A) Example of fundamental frequency representation of two tokens of the tonal contrast used in Liu and Kager (2014 , 2017a , b , c ); (B) spectrograms of the tonal contrast shown in Figure 1 ( x -axis: duration; y -axis: amplitude). …”
Section: Methodsmentioning
confidence: 99%
“…For example, while Dutch infants reached adult-like sensitivity to linguistic pitch by 18 months, simultaneous-bilingual Dutch infants achieved approximately the same level of sensitivity 6 months earlier (Liu & Kager, 2014, 2017a. Moreover, when hearing a violin contrast that differed solely in F0, 9-month-old Dutch bilingual infants showed more robust perceptual sensitivity than their monolingual peers (Liu & Kager, 2017b). Studies have reported that listeners' auditory system encodes F0 more robustly and efficiently if they grow up in a bilingual environment, promoting experience-dependent neural plasticity (Krizman et al, 2012).…”
mentioning
confidence: 99%